(untitled) - Mamatkul Juraev , Tokhtamurod Kochkarov , Hamrayeva Gulmira (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The article describes how the ancient epic plots about Tomaris and Shirak were formed in the folklore performance traditions of the Sak-Massaget tribes.